COLLABORATIVE GOVERNANCE IN IMPROVING THE CULINARY AND SASIRANGAN INDEPENDENCE COACHING PROGRAM IN CLASS IIB BANJARBARU PRISON INSTITUTION - Erwin Aditya Putra; Meitisa Vanya Simanjuntak (Journal of Management Small and Medium Enterprises (SME's))
This study evaluates collaborative governance in the culinary and Sasirangan self-reliance coaching program at the Banjarbaru Class IIB Correctional Institution. This research uses qualitative methods to obtain accurate study results. The research shows that effective face-to-face dialogue, strong trust, and commitment to the process have supported the program's success. Good communication between the Correctional Institution, CV. 2 Putra Mandiri Yana Snack & Food Banjarbaru, and Lembaga Pelatihan Keterampilan (LPK) Melati facilitated understanding and productive collaboration. The program has also shown progress through positive interim outcomes, such as inmate certification in Sasirangan making. However, constraints such as budget limitations and human resource issues, including lack of inmate motivation and officer understanding, hinder the effectiveness of the program. Despite progress, these issues need to be addressed to achieve optimal long-term results. This research underscores the importance of communication and resource support in the implementation of self-reliance coaching programs.